Potency of Agroindustrial Wastewaters for Increasing Dissolution of Phosphate Rock Fertilizers - Ainin Niswati; Sri Yusnaini; . Sarno (UNIVERSITY OF LAMPUNG, 2014)
Agroindustrial wastewaters were considered not maximum used in Lampung Province since it has acidic properties that can be used as an acid solvent. This study aimed was to explore the most potential agroindustrial wastewaters in dissolving phosphate rock by acidulation in the laboratory scale. The experimen were arranged by factorial i.e. first factor were phosphate rock origin (Sukabumi, west Java and Selagailingga, central Lampung) and second factor was kinds of solvent (agroindustrial wastewaters of pineapple, tapioca, tofu industry, and palm oil as well as a conventional acid solvent such as HCl, H2SO4, and CH3COOH). The incubation process were 0, 1, 2, and 3 month. The results showed that agroindustrial wastewaters that have highest potency for solubizing phosphate rock was industrial tofu wastewaters and followed by industrial wastewaters of tapioca, palm oil, and pineapple. Both the conventional acid and agroindustrial wastewaters solvent have a big potency for solubilize phosphate rock, however, its highest soluble P-value was not match with the ISO criteria for phosphate fertilizers Quality I (SNI) because it has not reached the solubility of 80% of its total P2O5, but has been qualified as a fertilizer both the quality phosphate A, B, and C (SNI).Keywords: Acidulation, agroindustrial wastewater, P fertilizer, phosphate rock [How to Cite: Ainin N, S Yusnaini and Sarno. 2014. Potency of Agroindustrial Wastewaters to Increase the Dissolution of Phosphate Rock Fertilizers. J Trop Soils 19: 43-51. Doi: 10.5400/jts.2014.19.1.43]